The Effectiveness of Case-Based Learning to Improve the Collaboration and Communication Skills of Early Childhood Education Students - Silitubun, Evaristus; Isro’iyah, Latifatul; Pakpahan, Emma Martina; Hidayati, Nur; Panggabean, Tongam E; Santosa, Tomi Apra; Hendrik, Hendrik; Ilwandri, Ilwandri; Nugraha, Aat Ruchiat; Sjroida, Diah Fatma (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study investigates the impact of case-based learning (CBL) on enhancing collaboration and communication skills among early childhood education (ECE) students. A meta-analysis was conducted using 25 effect sizes from studies published between 2022 and 2024, involving 1,056 participants and sourced from databases such as ERIC, ScienceDirect, Google Scholar, and Wiley. The JSAP application facilitated statistical analysis. Results indicate that CBL significantly outperforms conventional learning methods in fostering collaboration and communication, evidenced by a high summary effect size of 1.013. CBL offers an interactive, student-centered approach that places students in real-life scenarios, encouraging active participation, teamwork, and problem-solving skills. Through intensive group discussions and collaborative activities, students learn to articulate ideas, respect diverse perspectives, and engage constructively in group settings. These findings underscore CBL’s potential as an effective pedagogical approach for developing essential interpersonal skills in ECE, which are critical for students' professional preparedness. Future studies should consider longitudinal impacts and cross-cultural contexts to validate these outcomes further.